A Comparative Analysis of Asymmetric Transmission across Monetary Policy Regimes on Interest Rate Pass-Through in Indonesia’s Banking Sector - Stefano, David; Wibowo, Buddi (PT Mattawang Mediatama Solution, 2025)
This study examines the interest rate pass-through mechanism in Indonesia by analyzing how changes in the central bank policy rate are transmitted to commercial bank lending and deposit rates. The research focuses on two monetary policy regimes implemented by Bank Indonesia, namely the BI 7-Day Reverse Repo Rate and the new BI Rate introduced after December 2023. Using monthly time-series data from August 2016 to January 2025, the study employs the Error Correction Model and Mean Adjusted Lag to evaluate both the short-term and long-term dynamics of interest rate transmission. The Johansen Cointegration Test is also applied to identify the existence of long-run equilibrium relationships between the policy rate and banking interest rates. The results show that the pass-through process is asymmetric, with lending rates responding more quickly to policy rate increases than deposit rates do to policy rate decreases. The analysis also reveals variation in the speed and completeness of pass-through across the different policy regimes. Specifically, the new BI Rate demonstrates a shorter lag in transmission, suggesting improved responsiveness of the interest rate channel under the updated framework. These findings highlight the evolving nature of monetary policy effectiveness in Indonesia’s financial system and provide a better understanding of interest rate dynamics in an emerging market context.